Weather-Driven Loss Modeling for Rice Farmers' Losses Using Cobb-Douglas and VaR-ES - Nurviana Nurviana; Amelia Amelia; Riezky Purnama Sari; Ulya Nabilla; Mawarni Mawarni; Masthura Masthura (ZERO: Jurnal Sains, Matematika dan Terapan, 2025)
Weather variability poses significant risks to rice production, leading to potential income losses for farmers and increased uncertainty in agricultural planning. This study integrates a Cobb-Douglas production function with Value at Risk (VaR) and Expected Shortfall (ES) measures to assess weather-driven production losses in Aceh Besar using secondary data on rainfall, temperature, and wind speed from 2010 to 2023. Rice production is first modeled to estimate output sensitivity to climatic factors, after which production losses are derived from forecast-based outcomes. Several candidate parametric probability distributions are fitted to the loss data, and the most suitable distribution is selected based on goodness-of-fit ranking. The results indicate that weather variables significantly reduce rice output and that the production process exhibits decreasing returns to scale. The selected distribution yields a potential loss of IDR 774,352 and an expected loss of IDR 940,160 per hectare at the 95% confidence level. These findings provide a quantitative basis for weather-based agricultural risk assessment and support evidence-based risk mitigation strategies for farmers and policymakers.